EFFECTIVE APPROACH IN TEACHING ENGLISH FOR THE SOCIETY MEMBERS IN BALI - I Nengah Sudipa (Universitas Negeri Padang, 2016)
Bali is one of the tourism destinations in Indonesia. The government keeps trying to maintain the natural and human resources for the sustainability of such a non-smoked industry. Some efforts have been done ever since, among others: protecting the tourism art-facts, providing infra-structure and stimulating society members to improve their tourism knowledge and foreign language skills. In order to improve their skills in mastering English- as a means of international communication-the local government, e.g. each regency establishes a group of tourism awareness, in every village called Kelompok Sadar Wisata (abbrev. Pokdarwis). This article aims at introducing the effective Communicative approach, with RELUS techniques applied in the process of learning English as a Foreign Language. The training was attended by 40 members of Pokdarwis Mekar Bhuana in Petang village, Badung Regency. The materials were delivered in terms of conversational process using the techniques of: RELUS (R=read, LU =look up, S=say). This English-training was intensively given for 4 hours a day twice a week for 24 sessions (3 months). The materials include: greeting, farewell and special expressions, apologizing, request, invitation, suggestion and English for Tourism. The steps for each session were: orientation, drills, feedback and continuation. The result showed that generally all participants manage to speak actively to welcome the English speaking tourists coming to their respective villages